Association between psychosocial factors and adverse effects of light-to-moderate ambient heat in patients with chronic diseases: results of the prospective cohort study CLIMATE-II - Schäfer, Ingmar; Paucke, Valentina; Nothacker, Julia; Menzel, Agata; Döpfmer, Susanne; Hager, Klaus; Hueber, Susann; Karimzadeh, Arian; Kötter, Thomas; Löffler, Christin; Müller, Beate S.; Scherer, Martin; et al. (BMC Medicine, 2026)
Background: Global temperatures are increasing. Adaptation of health behavior could mitigate adverse effects of heat, but health benefits are probably limited and depend on the context. Therefore, other strategies are also needed. Our study aimed to identify adverse effects of light heat (> 27–32 °C) and moderate heat (> 32–40 °C) and to analyze whether psychosocial factors were associated with these effects. Methods: We conducted a prospective cohort study based on an access-restricted online survey and publicly available weather data. A total of 1810 individuals were contacted by 64 GP practices in 16 German federal states. Individuals were eligible if they were ≥ 18 years old and had ≥ 1 of 15 specific chronic diseases. Heat exposure was defined as thermal stress and operationalized by maximum temperatures and relative humidity assessed by 88 meteorological stations. Psychosocial factors were measured by standardized questionnaires assessing health literacy, self-efficacy, social support, risk expectations, and somatosensory amplification. Adverse effects of heat were operationalized by limitations in usual activities due to 14 specific symptoms reported at up to 12 follow-up assessments per participant. Data were analyzed by multivariable, multilevel, and mixed-effects linear regression. Results: A total of 4434 observations of 509 individuals were analyzed. Response rate was 28.1%. Participants had a mean age of 61.2 years (SD 13.7) and 240 participants (47.2%) identified themselves as women. Comparing the lowest range of heat exposure (11–15 °C) to the highest (37–40 °C), mean symptom burden increased by 79% from 3.7 (SD 5.3) to 6.7 (SD 6.0). Symptom burden was lower if participants reported better health literacy (− 0.15, 95% CI − 0.26/ − 0.05, P = 0.005), better general self-efficacy (− 0.20, 95% CI − 0.27/ − 0.14, P < 0.001), and perceived more social support (− 0.59, 95% CI − 1.07/ − 0.12, P = 0.015). Symptom burden was higher if participants reported more somatosensory amplification (0.18, 95% CI 0.13/0.24, P < 0.001) and expected a higher risk for adverse effects of heat (0.43, 95% CI 0.30/0.56, P < 0.001). We found significant effect modification (P = 0.041 through P < 0.001), indicating that the symptom burden related to light-to-moderate heat was more pronounced among patients with poorer psychosocial status. Conclusions: Light-to-moderate heat was associated with adverse effects. Health literacy, self-efficacy, and social support mitigated these effects, and negative expectations and the tendency to interpret benign bodily sensations as threatening amplified them. Trial registration: ClinicalTrials.gov NCT06407154.
CRIS-Team Scopus Importer:2026-02-06
Keywords: Ambient temperature; Chronic diseases; Climate change; Heat; Psychosocial factors; Risk expectations